FORMATION INFORMATICS COMPETENCЕ OF BACHELOR OF PHILOLOGY IN THE LEARNING PROCESS - Glushak, Oksana M. (Educological discourse, 2016)
In the article the features of formation of informatics competence of the bachelors of Philology in the process of teaching it disciplines. Analyzed the concept of "information competence", " informatics competence ". Defines the components of informatics competence in the context of functionally-active field bachelor's degree in Philology. The study determined that in the process of formation of information competence bachelors in Philology should focus on: system personal important beliefs that determine the need for obtaining, processing and transmitting of information data, the use of ICT at the stage of training and future professional activity; system of knowledge, abilities and skills for technical, system, software component of ICT, a range of abilities and skills of students to work with informational data, the use of ICT in educational and vocational activity; self-diagnosis of the impact of its activities during training and during professional work.